Harship Doctrine Regarding Fulfillment of the Performance of an Agreement - Dian Cahayani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In contract law, performance fulfillment is a fundamental principle. However, in practice, unforeseen changes in circumstances can disrupt performance fulfillment. To address this, the doctrine of hardship is necessary to create a balance between performance fulfillment and unforeseen changes in circumstances. The aim of this research is to analyze the concept of the hardship doctrine in contract law and identify its impact on the interpretation and performance of contracts, as well as the protection of rights and fairness for parties bound by contractual agreements. The research method used is normative research method with a focus on analyzing the legal regulations that govern the hardship doctrine. The data sources include legal texts, regulations, court decisions, and relevant legal expert opinions, along with techniques such as legal document analysis, comparison, and drawing conclusions to generate a comprehensive understanding. In contract law, the hardship doctrine refers to the concept of unforeseen changes in circumstances significantly affecting contract performance. This doctrine allows parties to request contract modifications or terminations in situations that are no longer fair or feasible. It also impacts contract interpretation, as courts determine whether the changed circumstances meet the criteria for activating the doctrine. Although not fully regulated in Indonesian legislation, the Civil Code provides relevant legal grounds. It is important for contracting parties to understand the implications of the hardship doctrine and consider its inclusion in their agreements. The doctrine plays a crucial role in protecting the rights and ensuring fairness to parties bound by contractual agreements in Indonesia. It provides protection, flexibility, and considerations for social impact and public interests. However, its use should be limited, meet strict requirements, and align with applicable laws. Therefore, the hardship doctrine serves as an essential tool to maintain balance and justice in contract performance when used carefully and in compliance with relevant conditions.